Nanopatterned rGO/ZnO:Al seed layer for vertical growth of single ZnO nanorods. (18th June 2023) - Chalangar, Ebrahim; Mustafa, Elfatih; Nur, Omer; Willander, Magnus; Pettersson, Håkan
Abstract: In this work, we demonstrate a novel low-cost template-assisted route to synthesize vertical ZnO nanorod arrays on Si (100). The nanorods were grown on a patterned double seed layer comprised of reduced graphene oxide (rGO) and Al-doped ZnO nanoparticles. The seed layer was fabricated by spray-coating the substrate with graphene and then dip-coating it into a Al-doped ZnO sol–gel solution. The growth template was fabricated from a double-layer resist, spin-coated on top of the rGO/ZnO:Al seed layer, and patterned by colloidal lithography. The results show a successful chemical bath deposition of vertically aligned ZnO nanorods with controllable diameter and density in the nanoholes in the patterned resist mask. Our novel method can presumably be used to fabricate electronic devices on virtually any smooth substrate with a thermal budget of 1 min at 300 °C with the seed layer acting as a conductive strain-relieving back contact. The top contact can simply be made by depositing a suitable transparent conductive oxide or metal, depending on the specific application.